Tracking food safety budgets in Kenya - Guthiga, Paul M.; Kirui, Leonard; Karugia, Joseph T. (International Livestock Research Institute, 2020)
Infographic created for Voice for Change Partnership, Food and Nutrition Security Dissemination Forum: Evidence for Policy, Advocacy and Partnerships, Online Webinar, 8th July 2020